Anode for non-aqueous electrolyte storage element, non-aqueous electrolyte storage element, and method for manufacturing the same

A coating layer containing nitrogen, silicon, or phosphorus compounds on the negative electrode of non-aqueous electrolyte storage elements prevents dendrite growth, thereby reducing micro-short circuits and improving element stability.

JP7654981B2Active Publication Date: 2025-04-02GS YUASA CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021004938
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-15
Publication Date
2025-04-02
Estimated Expiration
2041-01-15

AI Technical Summary

Technical Problem

Non-aqueous electrolyte storage elements using metallic lithium as the negative electrode active material are prone to micro-short circuits due to dendrite growth, which current protective films fail to adequately prevent.

Method used

A negative electrode with a coating layer containing compounds like nitrogen, silicon, and phosphorus, or their reaction products with metallic lithium, is applied to suppress dendrite growth and micro-short circuits.

Benefits of technology

The coating layer effectively delays and suppresses the occurrence of micro-short circuits during charging and discharging, enhancing the stability of the non-aqueous electrolyte storage elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654981000002
    Figure 0007654981000002
  • Figure 0007654981000003
    Figure 0007654981000003
  • Figure 0007654981000001
    Figure 0007654981000001
Patent Text Reader

Abstract

To provide a negative electrode for a nonaqueous electrolyte power storage device and a nonaqueous electrolyte power storage device, which enable the suppression of occurrence of a fine short circuit, and production methods thereof.SOLUTION: A negative electrode for a nonaqueous electrolyte power storage device comprises: a negative electrode active material layer containing lithium metal; and a coating layer coating at least a part of the negative electrode active material layer. The coating layer contains a compound which includes at least one kind of nitrogen, silicon and phosphorus and which can react with the lithium metal, or a reaction product of the compound and the lithium metal.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, and a method for producing the same. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary battery generally has a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and is configured to charge and discharge by transferring ions between the electrodes. In addition, as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used. Metallic lithium is known as a negative electrode active material having a high energy density and used in non-aqueous electrolyte storage elements (see Patent Documents 1 and 2). Patent Document 3 also describes a method of providing a protective film on the surface of metallic lithium using a fluorine-containing polymer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-100065 A [Patent Document 2] Japanese Patent Application Publication No. 07-245099 [Patent Document 3] JP 2003-36842 A Summary of the Invention [Problem to be solved by the invention]

[0004] In non-aqueous electrolyte storage elements using metallic lithium as the negative electrode active material, such as lithium batteries, metallic lithium may be deposited in a dendritic form on the surface of the negative electrode during charging (hereinafter, metallic lithium in a dendritic form will be referred to as "dendrite"). When this dendrite grows and penetrates the separator to come into contact with the positive electrode, it causes a micro-short circuit. For this reason, non-aqueous electrolyte storage elements containing metallic lithium as the negative electrode active material have the disadvantage that they are prone to micro-short circuits due to repeated charging and discharging. Even when a negative electrode provided with a protective film as in Patent Document 3 is used, the effect of suppressing the occurrence of micro-short circuits is not sufficient.

[0005] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide a negative electrode for a nonaqueous electrolyte storage element, which is capable of suppressing the occurrence of micro-short circuits, a nonaqueous electrolyte storage element, and methods for manufacturing the same. [Means for solving the problem]

[0006] One aspect of the present invention is a negative electrode (A) for a nonaqueous electrolyte storage element, comprising a negative electrode active material layer containing metallic lithium, and a coating layer coating at least a portion of the negative electrode active material layer, the coating layer containing a compound that contains at least one of nitrogen, silicon, and phosphorus and is capable of reacting with the metallic lithium, or a reaction product of the compound and the metallic lithium.

[0007] Another aspect of the present invention is a negative electrode (B) for a nonaqueous electrolyte storage element, comprising a negative electrode active material layer containing metallic lithium, and a coating layer coating at least a portion of the negative electrode active material layer, wherein the coating layer contains an oxoacid, oxoacid salt, or oxide containing at least one of nitrogen, silicon, and phosphorus, or a reaction product of any of these with the metallic lithium.

[0008] Another aspect of the present invention is a method (A) for producing a negative electrode for a nonaqueous electrolyte storage element, comprising contacting a negative electrode active material layer containing metallic lithium with a material for forming a coating layer, the material including a compound that contains at least one of nitrogen, silicon, and phosphorus and is capable of reacting with the metallic lithium.

[0009] Another aspect of the present invention is a method (B) for producing a negative electrode for a nonaqueous electrolyte storage element, comprising contacting a negative electrode active material layer containing metallic lithium with a coating layer-forming material containing an oxoacid, oxoacid salt, or oxide containing at least one of nitrogen, silicon, and phosphorus.

[0010] Another aspect of the present invention is a nonaqueous electrolyte electricity storage element including the negative electrode (A) or negative electrode (B) according to an aspect of the present invention.

[0011] Another aspect of the present invention is a method for producing a nonaqueous electrolyte storage element, comprising producing a nonaqueous electrolyte storage element using the negative electrode (A) or negative electrode (B) according to an aspect of the present invention, or a negative electrode obtained by the negative electrode production method (A) or negative electrode production method (B) according to an aspect of the present invention. Effect of the Invention

[0012] According to one aspect of the present invention, it is possible to provide a negative electrode for a nonaqueous electrolyte storage element, which is capable of suppressing the occurrence of micro-short circuits, a nonaqueous electrolyte storage element, and a method for producing the same. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is an external perspective view showing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] First, an outline of the negative electrode for a nonaqueous electrolyte storage element, the method for manufacturing the negative electrode for a nonaqueous electrolyte storage element, the nonaqueous electrolyte storage element, and the method for manufacturing the nonaqueous electrolyte storage element disclosed in this specification will be described.

[0015] A negative electrode for a non-aqueous electrolyte storage element according to one embodiment of the present invention is a negative electrode (A) for a non-aqueous electrolyte storage element, comprising a negative electrode active material layer containing metallic lithium, and a coating layer coating at least a part of the negative electrode active material layer, the coating layer containing at least one of nitrogen, silicon, and phosphorus and a compound capable of reacting with the metallic lithium, or a reaction product of the compound and the metallic lithium.

[0016] The negative electrode (A) can suppress the occurrence of micro-short circuit caused by repeated charging and discharging of the nonaqueous electrolyte storage element. That is, in the nonaqueous electrolyte storage element provided with the negative electrode (A), the occurrence of micro-short circuit caused by repeated charging and discharging is delayed. The reason for this is unclear, but the following reason is presumed. It is considered that at least a part of the compound containing at least one of nitrogen, silicon, and phosphorus in the coating layer and capable of reacting with metallic lithium reacts with metallic lithium to form a reaction product by contacting metallic lithium on the surface of the negative electrode active material layer by covering at least a part of the negative electrode active material layer. In addition, this reaction is considered to proceed during charging and discharging of the nonaqueous electrolyte storage element. It is presumed that the coating layer that covers at least a part of the negative electrode active material layer contains a reaction product between the compound containing at least one of nitrogen, silicon, and phosphorus and metallic lithium, or is capable of forming such a reaction product, so that the coating layer becomes homogeneous and of good quality, and thus the growth of dendrites on the surface of the negative electrode is suppressed.

[0017] The compound is preferably an oxoacid, an oxoacid salt or an oxide, which makes the coating layer more uniform and of better quality and further suppresses the occurrence of micro-short circuits.

[0018] A negative electrode for a non-aqueous electrolyte storage element according to another embodiment of the present invention is a negative electrode (B) for a non-aqueous electrolyte storage element, comprising a negative electrode active material layer containing metallic lithium, and a coating layer coating at least a part of the negative electrode active material layer, the coating layer containing an oxoacid, oxoacid salt, or oxide containing at least one of nitrogen, silicon, and phosphorus, or a reaction product of any of these with the metallic lithium.

[0019] The negative electrode (B) can suppress the occurrence of micro-short circuits that accompany repeated charging and discharging of the nonaqueous electrolyte storage element. Although the reason for this is unclear, it is presumed that, like the above-mentioned negative electrode (A), the coating layer that covers at least a part of the negative electrode active material layer containing metallic lithium contains an oxo acid, an oxo acid salt, an oxide, or a reaction product of these with metallic lithium, containing at least one of nitrogen, silicon, and phosphorus, making the coating layer homogeneous and of good quality, thereby suppressing the growth of dendrites on the surface of the negative electrode.

[0020] In some cases, it may be preferable that the coating layers of the negative electrode (A) and the negative electrode (B) further contain a binder. When the coating layer further contains a binder, a compound containing at least one of nitrogen, silicon, and phosphorus is sufficiently fixed to the negative electrode active material layer. In addition, depending on the type of compound contained in the coating layer, the occurrence of a micro-short circuit can be further suppressed. For example, when a compound that dissolves in a non-aqueous electrolyte is used in the coating layer, the coating layer contains a binder, and the dissolution rate of the compound in the non-aqueous electrolyte is adjusted, so that the occurrence of a micro-short circuit can be further delayed.

[0021] The binder is preferably a fluororesin. When the binder is a fluororesin, the coating layer becomes more uniform and of better quality, and the compound used is more sufficiently fixed to the negative electrode active material layer, so that the occurrence of a micro-short circuit can be further suppressed.

[0022] In some cases, it may be preferable that the coating layers of the negative electrode (A) and the negative electrode (B) are substantially free of binder. In such cases, the coating layer containing the reaction product of a specific compound and metallic lithium becomes more homogeneous and of good quality, and the coating layer has a low resistance, making it difficult for current concentration to occur, thereby making it possible to further suppress the occurrence of micro-short circuits. Note that the coating layer being substantially free of binder means that the binder content in the coating layer is 1% by mass or less.

[0023] A method (A) for producing a negative electrode for a nonaqueous electrolyte storage element according to one embodiment of the present invention is a method for producing a negative electrode for a nonaqueous electrolyte storage element, comprising contacting a negative electrode active material layer containing metallic lithium with a material for forming a coating layer, the material including a compound that contains at least one of nitrogen, silicon, and phosphorus and is capable of reacting with the metallic lithium.

[0024] According to the production method (A), it is possible to produce a negative electrode that can suppress the occurrence of micro-short circuits that occur during repeated charging and discharging of a nonaqueous electrolyte electricity storage element.

[0025] A method (B) for producing a negative electrode for a nonaqueous electrolyte storage element according to another embodiment of the present invention includes contacting a negative electrode active material layer containing metallic lithium with a coating layer-forming material containing an oxoacid, oxoacid salt, or oxide containing at least one of nitrogen, silicon, and phosphorus.

[0026] The production method (B) also makes it possible to produce a negative electrode that can suppress the occurrence of micro-short circuits that occur during repeated charging and discharging of a nonaqueous electrolyte electricity storage element.

[0027] A nonaqueous electrolyte electricity storage element according to an embodiment of the present invention is a nonaqueous electrolyte electricity storage element including the negative electrode (A) or negative electrode (B) according to an embodiment of the present invention.

[0028] The nonaqueous electrolyte storage element includes the negative electrode (A) or the negative electrode (B) according to one aspect of the present invention, and therefore is prevented from causing micro-short circuits that may occur during repeated charging and discharging.

[0029] A method for producing a nonaqueous electrolyte storage element according to one embodiment of the present invention includes producing a nonaqueous electrolyte storage element using the negative electrode (A) or negative electrode (B) according to one embodiment of the present invention, or a negative electrode obtained by the negative electrode production method (A) or negative electrode production method (B) according to one embodiment of the present invention.

[0030] According to this manufacturing method, a nonaqueous electrolyte electricity storage element can be manufactured in which the occurrence of micro-short circuits caused by repeated charging and discharging is suppressed.

[0031] Hereinafter, a negative electrode for a nonaqueous electrolyte storage element according to one embodiment of the present invention, a method for manufacturing a negative electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, and a method for manufacturing a nonaqueous electrolyte storage element will be described in order.

[0032] <Negative electrode for non-aqueous electrolyte storage element> A negative electrode for a non-aqueous electrolyte storage element according to one embodiment of the present invention includes a negative electrode substrate, a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer, and a coating layer that coats at least a portion of the negative electrode active material layer. That is, the negative electrode has a laminated structure in which at least three layers, the negative electrode substrate, the negative electrode active material layer, and the coating layer, are laminated in this order. The negative electrode active material layer and the coating layer may be laminated on only one surface of the negative electrode substrate, or may be laminated on both surfaces of the negative electrode substrate.

[0033] (Negative electrode substrate) The negative electrode substrate has electrical conductivity. The term "electrically conductive" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 "Non-conductive" means that the volume resistivity is 10 7 It means that the resistance is more than Ω·cm. Metals such as copper, nickel, stainless steel, nickel-plated steel, etc., or alloys thereof are used as the material of the negative electrode substrate, and copper or copper alloys are preferred. The negative electrode substrate may be formed in the form of foil, vapor deposition film, etc., and foil is preferred from the viewpoint of cost. In other words, copper foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0034] The average thickness of the negative electrode substrate is preferably 2 μm or more and 35 μm or less, more preferably 3 μm or more and 30 μm or less, even more preferably 4 μm or more and 25 μm or less, and particularly preferably 5 μm or more and 20 μm or less. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate while increasing the energy density per volume of the nonaqueous electrolyte storage element. The "average thickness" refers to the value obtained by dividing the punched mass when a substrate of a predetermined area is punched out by the true density and punched area of ​​the substrate. The same applies to the "average thickness" of the positive electrode substrate described below.

[0035] (Middle class) The intermediate layer is a coating layer on the surface of the negative electrode substrate, and contains conductive particles such as carbon particles to reduce the contact resistance between the negative electrode substrate and the negative electrode active material layer. The configuration of the intermediate layer is not particularly limited, and can be formed, for example, from a composition containing a resin binder and conductive particles.

[0036] (Negative electrode active material layer) The negative electrode active material layer contains metallic lithium. The metallic lithium is a component that functions as a negative electrode active material. The metallic lithium may exist as pure metallic lithium substantially consisting of lithium alone, or may exist as a lithium alloy containing other metal components. Examples of the lithium alloy include a lithium silver alloy, a lithium zinc alloy, a lithium calcium alloy, a lithium aluminum alloy, a lithium magnesium alloy, and a lithium indium alloy. The lithium alloy may contain a plurality of metal elements other than lithium.

[0037] The negative electrode active material layer may be a layer consisting essentially of metallic lithium. The content of metallic lithium in the negative electrode active material layer may be 90% by mass or more, may be 99% by mass or more, or may be 100% by mass.

[0038] The negative electrode active material layer may be a lithium foil or a lithium alloy foil. The negative electrode active material layer may be a non-porous layer (solid layer). The negative electrode active material layer may also be a porous layer having particles containing metallic lithium. The average thickness of the negative electrode active material layer is preferably 5 μm to 1,000 μm, more preferably 10 μm to 500 μm, and even more preferably 30 μm to 300 μm.

[0039] (covering layer) The coating layer covers at least a part of the negative electrode active material layer. That is, the negative electrode active material layer may have an exposed part. However, the coating layer preferably covers 50% or more of the area of ​​the outer surface (surface other than the surface in contact with the negative electrode base material or intermediate layer) of the negative electrode active material layer, more preferably covers 70% or more, and even more preferably covers 90% or more, and further preferably covers 99% or more.

[0040] The coating layer contains a compound containing at least one of nitrogen, silicon and phosphorus, or a reaction product of the above compound with metallic lithium.

[0041] In the first embodiment of the negative electrode, the compound containing at least one of nitrogen, silicon, and phosphorus is a compound containing at least one of nitrogen, silicon, and phosphorus and capable of reacting with metallic lithium. The compound containing at least one of nitrogen, silicon, and phosphorus and capable of reacting with metallic lithium may be a compound in which the oxidation number of nitrogen, silicon, or phosphorus is a positive value. Examples of such compounds include oxoacids containing nitrogen, silicon, or phosphorus, salts of these oxoacids, and oxides of nitrogen, silicon, or phosphorus.

[0042] Examples of nitrogen-containing oxoacids include nitric acid and nitrous acid. Examples of silicon-containing oxoacids include silicic acid. Examples of phosphorus-containing oxoacids include phosphoric acid and phosphorous acid. Examples of salts of these oxoacids include alkali metal salts such as lithium salts and sodium salts, alkaline earth metal salts such as magnesium salts and calcium salts, aluminum salts, and salts of transition metals such as iron, copper, and silver. Examples of the oxides of nitrogen include nitric oxide and nitrogen dioxide. Examples of the oxides of silicon include silicon monoxide and silicon dioxide. Examples of the oxides of phosphorus include diphosphorus pentoxide.

[0043] When a compound containing at least one of nitrogen, silicon, and phosphorus is in a gaseous state at room temperature, it reacts with metallic lithium when it comes into contact with the surface of a negative electrode active material layer containing metallic lithium, and the reaction product can form a coating layer.

[0044] As the nitrogen-containing compound, oxoacids and oxoacid salts are preferred, and oxoacid salts are more preferred. As the nitrogen-containing compound, nitrous acid and nitrite salts may be more preferred, nitrite salts are more preferred, and alkali metal salts of nitrous acid are even more preferred. The phosphorus-containing compound is preferably an oxoacid or an oxoacid salt, more preferably an oxoacid, and more preferably a phosphorous acid or a phosphite salt, further preferably phosphorous acid. The silicon-containing compound is preferably an oxide of silicon. When such a compound or a reaction product of such a compound with metallic lithium is contained in the coating layer, the effect of suppressing the occurrence of micro-short circuits is enhanced.

[0045] In a second embodiment of the negative electrode, the compound containing at least one of nitrogen, silicon, and phosphorus is an oxoacid, oxoacid salt, or oxide containing at least one of nitrogen, silicon, and phosphorus. In this embodiment, these compounds do not need to be capable of reacting with metallic lithium, but are preferably compounds capable of reacting with metallic lithium. Specific and suitable examples of the oxoacid, oxoacid salt, or oxide used in the second embodiment include the oxoacids, oxoacid salts, or oxides exemplified in the first embodiment described above.

[0046] A part or all of the compound containing at least one of nitrogen, silicon and phosphorus used in forming the coating layer may be present in the coating layer as it is. However, it is considered that the compound in the first embodiment reacts by contacting with the negative electrode active material layer containing metallic lithium. Therefore, a part or all of the compound used in forming the coating layer may be present in the coating layer in the form of a reaction product between metallic lithium and the compound.

[0047] The total content of the compound containing at least one of nitrogen, silicon, and phosphorus and the reaction product of the compound and metallic lithium in the coating layer may be 1% by mass or more and 100% by mass or less. The lower limit of the total content may be 5% by mass, 20% by mass, 50% by mass, 80% by mass, 90% by mass, 95% by mass, 99% by mass, or 99.9% by mass. When the total content of the compound containing at least one of nitrogen, silicon, and phosphorus and the reaction product of the compound and metallic lithium in the coating layer is high, the coating layer formed is more homogeneous and good, and the occurrence of micro-short circuit may be more suppressed. For example, when the compound containing at least one of nitrogen, silicon, and phosphorus is at least one of an oxo acid and an oxide, the content of the compound and the reaction product of the compound and metallic lithium tends to be high. The upper limit of the content may be 50% by mass or 30% by mass.

[0048] The coating layer may further include a binder. For example, when a compound that dissolves in a non-aqueous electrolyte is used in the coating layer, the coating layer may contain a binder to adjust the dissolution rate of the compound in the non-aqueous electrolyte, thereby further delaying the occurrence of a micro-short circuit. Examples of compounds that dissolve in a non-aqueous electrolyte include salts such as oxoacid salts containing at least one of nitrogen, silicon, and phosphorus, and specifically LiNO 3 Examples include:

[0049] Examples of the binder include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc. As the binder, fluororesins are preferred, and PVDF is more preferred.

[0050] When the coating layer contains a binder, the content of the binder in the coating layer is, for example, preferably 10% by mass or more and 99% by mass or less, more preferably 50% by mass or more and 95% by mass or less. When the content of the binder in the coating layer is within the above range, a compound containing at least one of nitrogen, silicon, and phosphorus is sufficiently fixed to the negative electrode active material layer. In addition, when a compound that dissolves in a non-aqueous electrolyte is used in the coating layer, the content of the binder in the above range can appropriately adjust the dissolution rate of the compound in the non-aqueous electrolyte.

[0051] The binder content in the coating layer may be preferably 30% by mass or less, 10% by mass or less, 1% by mass or less, 0.1% by mass or less, or even 0% by mass. In addition, it may be preferable that the coating layer does not substantially contain a binder. For example, when the compound containing at least one of nitrogen, silicon, and phosphorus is at least one of an oxo acid and an oxide, the lower the binder content, the more homogeneous and high-quality the coating layer becomes, and the coating layer has a lower resistance, making it difficult for current concentration to occur, and thus the occurrence of micro-short circuit tends to be more suppressed.

[0052] The coating layer may not substantially contain a crosslinked polymerizable compound. In the negative electrode, even if the coating layer does not substantially contain a crosslinked polymerizable compound, the use of a compound containing at least one of nitrogen, silicon, and phosphorus can suppress the occurrence of micro-short circuiting accompanying repeated charging and discharging of the nonaqueous electrolyte storage element. The content of the crosslinked polymerizable compound in the coating layer may be preferably 10% by mass or less, more preferably 3% by mass or less, 1% by mass or less, or 0% by mass. By setting the content of the crosslinked polymerizable compound in the coating layer to the above upper limit or less, productivity can be increased and production costs can be suppressed.

[0053] <Method of manufacturing a negative electrode for a non-aqueous electrolyte storage element> A method for producing a negative electrode for a non-aqueous electrolyte storage element according to one embodiment of the present invention includes, for example, laminating a negative electrode active material layer containing metallic lithium on a negative electrode substrate directly or via an intermediate layer (step 1), and contacting the negative electrode active material layer with a material for forming a coating layer containing a compound containing at least one of nitrogen, silicon, and phosphorus (step 2).

[0054] The above step 1 can be carried out by a conventionally known method. Specifically, for example, the negative electrode active material layer containing metallic lithium can be laminated on the negative electrode substrate directly or via an intermediate layer, and pressed. The negative electrode active material layer containing metallic lithium can be a lithium foil or a lithium alloy foil.

[0055] In the above step 2, a material for forming a coating layer is brought into contact with the exposed surface of the negative electrode active material layer in the laminate of the negative electrode base material and the negative electrode active material layer obtained in the above step 1. The material for forming a coating layer usually further contains a dispersion medium in addition to a compound containing at least one of nitrogen, silicon, and phosphorus, and may further contain a binder.

[0056] In a first embodiment of the method for producing the negative electrode, the compound containing at least one of nitrogen, silicon, and phosphorus is a compound containing at least one of nitrogen, silicon, and phosphorus and capable of reacting with metallic lithium. In a second embodiment of the method for producing the negative electrode, the compound containing at least one of nitrogen, silicon, and phosphorus is an oxo acid, oxo acid salt, or oxide containing at least one of nitrogen, silicon, and phosphorus. Specific examples and suitable examples of these compounds are the same as those exemplified as specific examples and suitable examples of the compound containing at least one of nitrogen, silicon, and phosphorus contained in the coating layer of the negative electrode according to one embodiment of the present invention.

[0057] The content of the compound containing at least one of nitrogen, silicon, and phosphorus in the solid content (components other than the dispersion medium) in the coating layer forming material may be 1% by mass or more and 100% by mass or less. The content of the binder in the solid content (components other than the dispersion medium) in the coating layer forming material may be 0% by mass or more and 99% by mass or less.

[0058] As the dispersion medium of the material for forming the coating layer, an organic solvent such as N-methylpyrrolidone (NMP), toluene, etc. is preferably used. The content of the dispersion medium in the material for forming the coating layer is, for example, preferably 50% by mass or more and 99% by mass or less, more preferably 80% by mass or more and 96% by mass or less.

[0059] Specifically, the above step 2 can be carried out by the following procedure. A compound containing at least one of nitrogen, silicon and phosphorus, a dispersion medium, etc. are mixed to prepare a material for forming a coating layer. The prepared material for forming a coating layer is brought into contact with the surface of the negative electrode active material layer. The negative electrode active material layer (a laminate of the negative electrode active material layer and the film of the material for forming a coating layer) in contact with the material for forming a coating layer is dried. The material for forming a coating layer can be brought into contact with the negative electrode active material layer by applying the material for forming a coating layer or immersing the negative electrode active material layer in the material for forming a coating layer. Through these steps, a coating layer containing a compound containing at least one of nitrogen, silicon and phosphorus or a reaction product of the compound and metallic lithium is laminated on the surface of the negative electrode active material layer.

[0060] In addition, when the compound containing at least one of nitrogen, silicon, and phosphorus is a gas at room temperature, the material for forming the coating layer may be a gas consisting of only the compound, or a mixed gas of the compound and other components. In this case, for example, the material for forming the coating layer is sprayed onto the surface of the negative electrode active material layer, or the negative electrode active material layer is exposed to a gas atmosphere of the material for forming the coating layer, thereby contacting the material for forming the coating layer with the surface of the negative electrode active material layer to form a coating layer.

[0061] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element according to one embodiment of the present invention has a positive electrode, a negative electrode, and a nonaqueous electrolyte. Hereinafter, a nonaqueous electrolyte secondary battery (hereinafter, simply referred to as a "secondary battery") will be described as an example of a nonaqueous electrolyte storage element. The positive electrode and the negative electrode are usually stacked or wound alternately with a separator interposed therebetween to form an electrode body. This electrode body is housed in a container, and the container is filled with a nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. In addition, as the container, a known metal container, a resin container, or the like that is usually used as a container for a secondary battery can be used.

[0062] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. The intermediate layer of the positive electrode may have the same structure as the intermediate layer of the negative electrode.

[0063] The positive electrode substrate can be configured in the same manner as the negative electrode substrate, but the material used is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum and aluminum alloys are preferred in terms of the balance between potential resistance, high conductivity, and cost. In other words, aluminum foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085P and A3003P as specified in JIS-H-4000 (2014).

[0064] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the secondary battery.

[0065] The positive electrode active material layer is a layer formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture forming the positive electrode active material layer may contain optional components such as a conductive agent, a binder, a thickener, and a filler as necessary.

[0066] The positive electrode active material can be appropriately selected from known positive electrode active materials. As the positive electrode active material for a lithium ion secondary battery, a material capable of absorbing and releasing lithium ions is usually used. As the positive electrode active material, for example, α-NaFeO 2 Lithium transition metal composite oxides having a crystalline structure, lithium transition metal composite oxides having a spinel crystalline structure, polyanion compounds, chalcogen compounds, sulfur, etc. 2 As an example of a lithium transition metal composite oxide having a crystalline structure, Li[Li x Ni 1-x ]O 2 (0≦x<0.5), Li[Li x Ni γ Co 1-x-γ ]O 2 (0≦x<0.5, 0<γ<1), Li[Li x Co 1-x ]O 2 (0≦x<0.5), Li[Li x Ni γ Mn 1-x-γ ]O 2 (0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co 1-x-γ-β ]O 2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al1-x-γ-β ]O 2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1). Lithium transition metal composite oxides with spinel crystal structure include Li x Mn 2 O 4 , Li x Ni γ Mn 2-γ O 4 Examples of polyanion compounds include LiFePO 4 , LiMnPO 4 , LiNiPO 4 , LiCoPO 4 , Li 3 V 2 (PO 4 ) 3 , Li 2 MnSiO 4 , Li 2 CoPO 4 Examples of the chalcogen compound include titanium disulfide, molybdenum disulfide, and molybdenum dioxide. The atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0067] The positive electrode active material is preferably a lithium transition metal composite oxide, such as α-NaFeO 2 More preferably, the lithium transition metal composite oxide has a crystalline structure of the above type. The lithium transition metal composite oxide preferably contains nickel or manganese as a transition metal, and more preferably contains both nickel and manganese. The lithium transition metal composite oxide may further contain other transition metals such as cobalt. α-NaFeO 2In the lithium transition metal composite oxide having a crystalline structure, the molar ratio (Li / Me) of lithium (Li) to transition metal (Me) is preferably more than 1, more preferably 1.1 or more, and even more preferably 1.2 or more. By using such a lithium transition metal composite oxide, the electric capacity can be increased. In addition, in the case of a nonaqueous electrolyte storage element using such a positive electrode active material, it tends to be used at a high current density, and dendrites are usually easy to grow. Therefore, in the case of a nonaqueous electrolyte storage element having a positive electrode having the above lithium transition metal composite oxide, the effect of suppressing the occurrence of micro-short circuit can be more significantly enjoyed. In addition, the upper limit of the molar ratio (Li / Me) of lithium to transition metal is preferably 1.6, more preferably 1.5.

[0068] α-NaFeO 2 As the lithium transition metal composite oxide having a type crystal structure, a compound represented by the following formula (1) is preferable. Li 1+α Me 1-α O 2 (1) In formula (1), Me is a transition metal including Ni or Mn, and 0<α<1.

[0069] In formula (1), Me preferably contains Ni and Mn. Me preferably consists essentially of two elements, Ni and Mn, or three elements, Ni, Mn, and Co. Me may contain other transition metals.

[0070] In formula (1), the lower limit of the molar ratio of Ni to Me (Ni / Me) is preferably 0.1, more preferably 0.2. On the other hand, the upper limit of this molar ratio (Ni / Me) is preferably 0.5, more preferably 0.45. By setting the molar ratio (Ni / Me) within the above range, the energy density is improved.

[0071] In formula (1), the lower limit of the molar ratio of Mn to Me (Mn / Me) is preferably 0.5, more preferably 0.55. On the other hand, the upper limit of this molar ratio (Mn / Me) is preferably 0.75, more preferably 0.7. By setting the molar ratio (Mn / Me) in the above range, the energy density is improved.

[0072] In formula (1), the upper limit of the molar ratio of Co to Me (Co / Me) is preferably 0.3, more preferably 0.2. The molar ratio (Co / Me) or the lower limit of the molar ratio (Co / Me) may be 0.

[0073] In formula (1), the molar ratio of Li to Me (Li / Me), i.e., (1+α) / (1-α), is preferably greater than 1.0 (α>0), more preferably 1.1 or more, and even more preferably 1.2 or more. On the other hand, the upper limit of this molar ratio (Li / Me) is preferably 1.6, more preferably 1.5. By setting the molar ratio (Li / Me) in the above range, the discharge capacity is increased.

[0074] The lower limit of the content of the lithium transition metal composite oxide relative to all the positive electrode active materials is preferably 50 mass%, more preferably 80 mass%, and even more preferably 95 mass%. The content of the lithium transition metal composite oxide relative to all the positive electrode active materials may be 100 mass%.

[0075] The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. Here, the "average particle size" refers to a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).

[0076] In order to obtain particles of the positive electrode active material in a predetermined shape, a pulverizer, a classifier, etc. are used. As a pulverization method, for example, a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve, etc. can be used. When pulverizing, wet pulverization in which water or an organic solvent such as hexane is coexistent can also be used. As a classification method, a sieve, a wind classifier, etc. are used as necessary for both dry and wet methods.

[0077] The content of the positive electrode active material in the positive electrode active material layer is preferably 70% by mass to 98% by mass, more preferably 80% by mass to 97% by mass, and even more preferably 90% by mass to 96% by mass. By setting the content of the positive electrode active material in the above range, the electric capacity of the secondary battery can be increased.

[0078] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, and conductive ceramics. Examples of carbonaceous materials include graphite and carbon black. Examples of carbon black include furnace black, acetylene black, and ketjen black. Among these, carbonaceous materials are preferred from the viewpoint of electrical conductivity and coating properties. Among these, acetylene black and ketjen black are preferred. Examples of the shape of the conductive agent include powder, sheet, and fiber.

[0079] The content of the conductive agent in the positive electrode active material layer is preferably from 1% by mass to 40% by mass, more preferably from 2% by mass to 10% by mass. By setting the content of the conductive agent in the above range, the energy density of the secondary battery can be increased.

[0080] Specific examples of the binder include the binders mentioned above as components of the coating layer of the negative electrode.

[0081] The content of the binder in the positive electrode active material layer is preferably from 0.5% by mass to 10% by mass, more preferably from 1% by mass to 6% by mass. By setting the content of the binder in the above range, the active material can be stably held.

[0082] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. In addition, when the thickener has a functional group that reacts with lithium, it is preferable to deactivate this functional group in advance by methylation or the like. In one embodiment of the present invention, it may be preferable that the thickener is not contained in the positive electrode active material layer.

[0083] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. In one embodiment of the present invention, it may be preferable that the filler is not contained in the positive electrode active material layer.

[0084] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0085] (Negative electrode) The negative electrode of the nonaqueous electrolyte storage element according to one embodiment of the present invention is the negative electrode described above as the negative electrode for the nonaqueous electrolyte storage element according to one embodiment of the present invention.

[0086] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0087] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C in the atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C in the atmosphere. Examples of materials that have a mass loss of a predetermined amount or less when heated include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the energy storage element.

[0088] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0089] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polyethylene carbonate, polypropylene carbonate, polyvinyl carbonate, polyalkyl methacrylates such as polymethyl methacrylate, polyalkyl acrylates such as polymethyl acrylate, polyvinyl ethylene carbonate, polyvinyl acetate, polyvinylpyrrolidone, polymaleic acid and its derivatives, polyvinylidene fluoride, poly(vinylidene fluoride-co-hexafluoropropylene), polytetrafluoroethylene, etc. Copolymers containing two or more of the monomers constituting the above-mentioned polymers may be used, or a mixture of two or more polymers may be used. These polymers may also be combined with inorganic salts or ionic liquids. The use of a polymer gel has the effect of suppressing leakage. As the separator, a polymer gel may be used in combination with the porous resin film or nonwoven fabric as described above.

[0090] (Non-aqueous electrolyte) As the non-aqueous electrolyte, a non-aqueous electrolytic solution containing a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent is preferably used.

[0091] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.

[0092] As the non-aqueous solvent, it is preferable to use at least one of a cyclic carbonate and a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When a cyclic carbonate and a chain carbonate are used in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.

[0093] Examples of the cyclic carbonate include ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, vinylethylene carbonate, chloroethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, fluoromethylethylene carbonate, trifluoroethylethylene carbonate, styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. The number of carbon atoms in the cyclic carbonate may be, for example, 3 or more and 13 or less, or 7 or less, or 5 or less.

[0094] As the cyclic carbonate, from the standpoint of oxidation resistance and the like, fluorinated cyclic carbonates such as fluoroethylene carbonate, difluoroethylene carbonate, fluoromethylethylene carbonate, and trifluoroethylethylene carbonate are preferred.

[0095] Examples of the chain carbonate include diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, diphenyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, ethyl-2,2,2-trifluoroethyl carbonate, etc. The number of carbon atoms in the chain carbonate may be, for example, 3 or more and 13 or less, or 7 or less, or 5 or less.

[0096] As the chain carbonate, from the viewpoint of oxidation resistance and the like, fluorinated chain carbonates such as 2,2,2-trifluoroethyl methyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, and ethyl-2,2,2-trifluoroethyl carbonate are preferred.

[0097] The content of the carbonate relative to the total non-aqueous solvent is preferably 50 vol % or more and 100 vol % or less, more preferably 80 vol % or more, and in some cases further preferably 90 vol % or more, 95 vol % or more, or 99 vol % or more.

[0098] The non-aqueous solvent preferably contains a fluorinated solvent. The total content of the fluorinated solvent with respect to the total non-aqueous solvent is preferably 60% by volume or more, more preferably 90% by volume or more, even more preferably 99% by volume or more, and particularly preferably 100% by volume. The fluorinated solvent refers to a solvent (non-aqueous solvent) having a fluorine atom in the molecule, such as a fluorinated carbonate (a fluorinated linear carbonate and a fluorinated cyclic carbonate), a fluorinated ether, etc. In this way, by containing a fluorinated solvent, preferably by containing it at the above-mentioned lower limit or more, it is possible to further improve the suppression of micro-short circuit, oxidation resistance, etc.

[0099] The electrolyte salt is usually a lithium salt. Examples of the lithium salt include LiPF 6 , LiPO 2 F 2 , LiBF 4 , LiClO 4 , LiN(SO 2 F) 2 Inorganic lithium salts such as LiSO 3 CF 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ), LiC(SO2 CF 3 ) 3 , LiC(SO 2 C 2 F 5 ) 3 Among these, inorganic lithium salts are preferred, and LiPF 6 From the standpoint of oxidation resistance and the like, the electrolyte salt preferably contains a fluorine atom.

[0100] The content of the electrolyte salt in the non-aqueous electrolyte is 0.1 mol / dm 3 More than 2.5mol / dm 3 Less than 0.3 mol / dm is preferred. 3 More than 2.0mol / dm 3 Less than 0.5 mol / dm is more preferable. 3 More than 1.7mol / dm 3 More preferably, 0.7 mol / dm 3 More than 1.5mol / dm 3 The following is particularly preferable: By setting the content of the electrolyte salt within the above range, the ionic conductivity of the non-aqueous electrolyte can be increased.

[0101] The non-aqueous electrolyte may contain an additive, such as aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, and cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, and sulfuric acid. Examples of the additives include dimethyl, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, etc. These additives may be used alone or in combination of two or more.

[0102] The content of the additive in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive in the above range, it is possible to improve the capacity retention performance or the charge / discharge cycle performance after high-temperature storage, and to further improve safety.

[0103] The non-aqueous electrolyte may be a solid electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.

[0104] The solid electrolyte can be selected from any material that has ionic conductivity such as lithium, sodium, calcium, etc., and is solid at room temperature (e.g., 15° C. to 25° C.). Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, oxynitride solid electrolytes, polymer solid electrolytes, etc.

[0105] As the sulfide solid electrolyte, in the case of a lithium ion secondary battery, for example, Li 2 SP 2 S 5 , LiI-Li 2 SP 2 S 5 , Li 10 Ge-P 2 S 12 etc.

[0106] In the non-aqueous electrolyte storage element, the positive electrode potential at the end of charge voltage during normal use is 4.30 V vs. Li / Li + It is preferable that the value is 4.35V vs. Li / Li or more. + More preferably, it is 4.40V vs. Li / Li or more. + By setting the positive electrode potential at the end-of-charge voltage during normal use to the above lower limit or higher, it is possible to increase the discharge capacity and the energy density.

[0107] In addition, "normal use" refers to a case where the nonaqueous electrolyte storage element is used under charging conditions recommended or specified for the nonaqueous electrolyte storage element. For example, if a charger for the nonaqueous electrolyte storage element is provided, the "normal use" refers to a case where the nonaqueous electrolyte storage element is used using the charger.

[0108] The upper limit of the positive electrode potential at the end-of-charge voltage during normal use of the nonaqueous electrolyte storage element is, for example, 5.0 V vs. Li / Li + 4.8V vs. Li / Li + 4.7V vs. Li / Li + It may be.

[0109] Dendrites tend to grow easily when the current density during charging is high. Therefore, the nonaqueous electrolyte electricity storage element according to one embodiment of the present invention can be suitably applied to applications in which charging is performed at a high current density. Examples of such applications include power sources for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs), and power sources for charging regenerative power.

[0110] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.

[0111] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0112] <Configuration of Nonaqueous Electrolyte Electricity Storage Device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in automobile power sources such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., power sources for electronic devices such as personal computers and communication terminals, or power storage power sources, etc. In this case, the technology according to one embodiment of the present invention may be applied to at least one of the nonaqueous electrolyte storage elements included in the electricity storage unit.

[0113] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.

[0114] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> A method for producing a nonaqueous electrolyte storage element according to one embodiment of the present invention includes producing a nonaqueous electrolyte storage element using a negative electrode according to one embodiment of the present invention or a negative electrode obtained by a method for producing a negative electrode according to one embodiment of the present invention. The production method can be performed in the same manner as in the production of a conventionally known nonaqueous electrolyte storage element, except that a negative electrode according to one embodiment of the present invention or a negative electrode obtained by a method for producing a negative electrode according to one embodiment of the present invention is used as the negative electrode.

[0115] For example, a method for producing the nonaqueous electrolyte storage element includes preparing or producing a positive electrode, preparing or producing a negative electrode, preparing or preparing a nonaqueous electrolyte, preparing or producing a separator, laminating or winding the positive electrode and the negative electrode with the separator interposed therebetween to form an electrode assembly in which the positive electrode and the negative electrode (electrode assembly) are alternately stacked, housing the positive electrode and the negative electrode (electrode assembly) in a container, and injecting the nonaqueous electrolyte into the container. After injection, the injection port is sealed to obtain the nonaqueous electrolyte storage element.

[0116] <Other embodiments> The present invention is not limited to the above-described embodiments, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0117] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (lithium battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The nonaqueous electrolyte storage element of the present invention can also be applied to various nonaqueous electrolyte secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors. The nonaqueous electrolyte storage element of the present invention can also be applied to lithium-air batteries. EXAMPLES

[0118] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0119] [Example 1] (Preparation of positive electrode) As a positive electrode active material, α-NaFeO 2 It has a Li 1+α Me 1-α O 2 A lithium transition metal composite oxide represented by the formula (Me is a transition metal) was used. Here, the molar ratio of Li to Me, Li / Me, was 1.33, and Me was composed of Ni and Mn, and was contained in a molar ratio of Ni:Mn=1:2.

[0120] A positive electrode mixture paste was prepared using N-methylpyrrolidone (NMP) as a dispersion medium, containing the positive electrode active material, acetylene black (AB) as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio of 94:4.5:1.5 as solid contents. The positive electrode mixture paste was applied to one side of an aluminum foil as a positive electrode substrate, dried, and pressed to prepare a positive electrode with a positive electrode active material layer. The positive electrode had a current density of 5.1 mA / cm at 1 C. 2 It was designed and manufactured to be.

[0121] (Preparation of negative electrode) The nickel lead wire was sandwiched between two sheets of lithium foil (metallic lithium 100% by mass) with an average thickness of 300 μm as the negative electrode active material layer.3 PO 3 The material for forming the coating layer was prepared by mixing the above-mentioned PVDF as a binder and NMP as a dispersion medium in a mass ratio of 0.05:0.5:6.5. The material was heated at 45°C, applied to the surface of the lithium foil, and then dried to prepare a negative electrode in which a coating layer was laminated on the surface of the negative electrode active material layer containing metallic lithium.

[0122] (Preparation of non-aqueous electrolyte) LiPF was dissolved in a mixed solvent of fluoroethylene carbonate (FEC) and 2,2,2-trifluoroethyl methyl carbonate (TFEMC) in a volume ratio of 30:70. 6 to 1 mol / dm 3 to give a non-aqueous electrolyte.

[0123] (Fabrication of non-aqueous electrolyte storage element) The positive electrode and the negative electrode were laminated with a separator made of a microporous polyolefin film interposed therebetween to produce an electrode assembly. The electrode assembly was placed in a container made of a metal resin composite film, and the nonaqueous electrolyte was poured into the container, which was then sealed by heat welding to obtain the nonaqueous electrolyte storage element (lithium battery) of Example 1.

[0124] [Examples 2 to 5 and Comparative Example 1] A material for forming a coating layer was prepared with the types of additives and binders as shown in Table 1, and the negative electrodes and nonaqueous electrolyte storage elements of Examples 2 to 5 and Comparative Example 1 were obtained in the same manner as in Example 1, except that this material for forming a coating layer was used. In Examples 4 and 5, a negative electrode in which a coating layer was formed using a material for forming a coating layer that did not contain a binder was used to obtain a nonaqueous electrolyte storage element. In Comparative Example 1, a negative electrode in which a coating layer was formed using a material for forming a coating layer that did not contain an additive was used to obtain a nonaqueous electrolyte storage element.

[0125] (Initial charge / discharge) The obtained nonaqueous electrolyte storage element was initially charged and discharged under the following conditions. At 25°C, constant current and constant voltage charging was performed with a current of 0.1C and a charge end voltage of 4.6V. The charge end condition was that the current was 0.05C. Then, a rest period of 10 minutes was provided. Then, constant current discharging was performed with a current of 0.1C and a discharge end voltage of 2.0V, and then a rest period of 10 minutes was provided. This charge and discharge cycle was performed for two cycles.

[0126] (Charge-discharge cycle test) Next, the following charge-discharge cycle test was performed. At 25°C, constant current and constant voltage charging was performed with a current of 0.2C and a charge end voltage of 4.6V. The charge end condition was that the current was until 0.05C. After that, a rest period of 10 minutes was provided. Then, constant current discharging was performed with a current of 0.1C and a discharge end voltage of 2.0V, and then a rest period of 10 minutes was provided. This charge-discharge cycle was repeated, and the number of cycles until a micro-short circuit occurred was recorded. The results (number of cycles until a micro-short circuit occurred) are shown in Table 1.

[0127] [Table 1]

[0128] As shown in Table 1, the nonaqueous electrolyte storage elements of Examples 1 to 5, which are provided with a negative electrode having a coating layer formed using a coating layer-forming material containing a predetermined compound containing at least one of nitrogen, silicon, and phosphorus, were confirmed to have an excellent effect of suppressing the occurrence of a micro-short circuit, with the number of cycles until a micro-short circuit occurred exceeding 90. Among the Examples, the nonaqueous electrolyte storage elements of Examples 4 and 5, which are provided with a negative electrode having a binder-free coating layer formed using a binder-free coating layer-forming material, were confirmed to have an especially excellent effect of suppressing the occurrence of a micro-short circuit. [Industrial Applicability]

[0129] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0130] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. a negative electrode active material layer containing metallic lithium; a coating layer that covers at least a portion of the negative electrode active material layer; Equipped with the coating layer includes a compound capable of reacting with the metallic lithium or a reaction product between the compound and the metallic lithium, and a binder; the compound is an oxoacid or an oxoacid salt containing either nitrogen or phosphorus, or an oxide containing silicon, A negative electrode for a nonaqueous electrolyte storage element, comprising the coating layer in which the compound and the binder are mixed.

2. A negative electrode active material layer containing metallic lithium; a coating layer that covers at least a portion of the negative electrode active material layer; Equipped with the coating layer contains at least one compound selected from the group consisting of nitric acid, nitrous acid, phosphoric acid, phosphorous acid, nitrates, nitrites, phosphates, and phosphites, or a reaction product of the compound with the metallic lithium, A negative electrode for a non-aqueous electrolyte storage element, in which the coating layer is directly laminated on the negative electrode active material layer (excluding the cases where the coating layer contains silicon oxide, silicon sulfide, lithium oxide, and lithium sulfide).

3. A negative electrode active material layer containing metallic lithium; a coating layer that covers at least a portion of the negative electrode active material layer; Equipped with the coating layer contains a compound capable of reacting with the metallic lithium or a reaction product of the compound and the metallic lithium, the compound is an oxoacid or an oxoacid salt containing either nitrogen or phosphorus, A negative electrode for a nonaqueous electrolyte storage element, in which the coating layer is positioned as the outermost layer and is laminated directly on the negative electrode active material layer (excluding the cases where the coating layer contains silicon oxide, silicon sulfide, lithium oxide, and lithium sulfide).

4. The method includes contacting a negative electrode active material layer containing metallic lithium with a coating layer forming material containing a compound capable of reacting with the metallic lithium and a binder, the compound is an oxoacid or an oxoacid salt containing either nitrogen or phosphorus, or an oxide containing silicon, A method for producing a negative electrode for a non-aqueous electrolyte storage element, comprising mixing the compound and the binder in the coating layer-forming material.

5. A method of forming a coating layer comprising contacting a negative electrode active material layer containing metallic lithium with a material for forming a coating layer containing at least one compound selected from the group consisting of nitric acid, nitrous acid, phosphoric acid, phosphorous acid, nitrates, nitrites, phosphates, and phosphites; forming a coating layer based on the coating layer forming material; Equipped with A method for producing a negative electrode for a nonaqueous electrolyte storage element, in which the coating layer is directly laminated on the negative electrode active material layer (excluding the case where the material for forming the coating layer contains silicon oxide, silicon sulfide, lithium oxide, and lithium sulfide).

6. A method for producing a negative electrode for a nonaqueous electrolyte storage element, comprising the steps of: contacting a negative electrode active material layer containing metallic lithium with a coating layer forming material containing a compound capable of reacting with the metallic lithium; forming a coating layer based on the coating layer forming material; Equipped with the compound is an oxoacid or an oxoacid salt containing either nitrogen or phosphorus, A method for manufacturing a negative electrode for a nonaqueous electrolyte storage element, in which the coating layer is located as the outermost layer of the negative electrode and is laminated directly on the negative electrode active material layer (excluding the case where the material for forming the coating layer contains silicon oxide, silicon sulfide, lithium oxide, and lithium sulfide).

7. A non-aqueous electrolyte electricity storage element comprising the negative electrode according to claim 1 .

8. 7. A method for producing a nonaqueous electrolyte storage element, comprising: producing a nonaqueous electrolyte storage element by using the negative electrode according to any one of claims 1 to 3 or the negative electrode obtained by the method for producing a negative electrode according to any one of claims 4 to 6.

Citation Information

Patent Citations

  • Negative electrode for nonaqueous electrolyte type lithium secondary battery

    JP1995245099A

  • Manufacturing method of lithium metal anode protective coat for lithium battery

    JP2003036842A

  • Nonaqueous electrolyte secondary battery and its manufacturing method

    JP2005063731A

  • Negative electrode plate for nonaqueous secondary battery, and its manufacturing method

    JP2007227219A

  • Lithium secondary battery

    JP2016100065A